ABILITY OF GMELINA, KHAYA, MAHOGANY, PULAI AND SURIAN AGAINST SOLAR RADIATION AND ENVIRONMENTAL COMFORT INDEXES - Kurniadi, Yopi
The existence of urban forests will increase environmental comfort in urban communities. The level of comfort of the environment is influenced by air temperature, air humidity, sunlight radiation and wind speed. Each tree species has a different ability to respond to these factors. This study aims to measure the ability to reduce Soil heat Flux (G) and the level of environmental comfort based on Temperature Humadity Index (THI) on gmelina stands (Gmelina arborea), khaya (Khaya anthotheca), mahogany (Swietenia macrophylla), surian (Toona sinensis), and pulai (Alstonia scholaris), and analyze the relationship between G and canopy density. This research was conducted for 50 days, located at ITB Jatinangor campus, which is located at six locations, including gmelina stands (G. arborea) khaya (K. anthotheca) mahogany (S. macrophylla) surian (T. sinensis), pulai (A. scholaris), and open land as a control variable. The parameters measured were the microclimate conditions at each location, including air temperature, humidity, wind speed, sunlight intensity and evapotranspiration. The microclimate conditions in open land were used as a comparison material with five other stands. The analysis was done by calculating the energy balance of Nisbah Bowen and THI. Some of the variables measured are Net Radiation (Rn), Sensible Heat Flux (H), and Latent Heat Flux (?E). The results showed that the highest average Rn reduction ability was in khaya stands (93.43%), mahogany (93.31%), pulai (85.86%), surian (42.50%), and gmelina (34, 40%). The highest H reduction ability was in pulai stands (81.85%), mahogany (77.86%), khaya (77.60%), gmelina (75.05%) and kurian (60.99%). The highest evapotranspiration in surian stands (1.82 mm / day), gmelina (1.04 mm / day), pulai (0.91 mm / day), khaya (0.5 mm / day), and mahogany (0.48 mm / day). The highest ability to reduce G in mahogany stands (94.79%), khaya (94.12%), pulai (89.36%), surian (63.88%), and gmelina (36.86%). The relationship between G and canopy density is inversely proportional to the equation y = 231.38 - 220.35x with R2 = 0.6418. Mahogany and khaya stands have high THI indices, whereas pulai, gmelina and surian stands have medium THI. This indicates that the khaya and mahogany stands are the best stands in reducing solar radiation energy.